2022
DOI: 10.3390/ph16010062
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Anti-Nonalcoholic Fatty Liver Effect of High-Sulfated Ulva pertusa Polysaccharide

Abstract: The high-sulfated derivative of Ulva pertusa polysaccharide (HU), with unclear structure, has better anti-hyperlipidmia activity than U pertusa polysaccharide ulvan (U). In this study, we explore the main structure of HU and its therapeutic effect against nonalcoholic fatty liver disease (NAFLD). The main structure of HU was elucidated using FT-IR and NMR (13C, 1H, COSY, HSQC, HMBC). The anti-NAFLD activity of HU was explored using the high-fat diet mouse model to detect indicators of blood lipid and liver fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Our previous investigations have shown that HU synthesized under this condition has good hypolipidemic activity, thus we applied the same methodology for subsequent experiments, including this one. 20,33…”
Section: Sulfate Contents Of Hu and Umentioning
confidence: 99%
“…Our previous investigations have shown that HU synthesized under this condition has good hypolipidemic activity, thus we applied the same methodology for subsequent experiments, including this one. 20,33…”
Section: Sulfate Contents Of Hu and Umentioning
confidence: 99%